Latin American Universities: Between Tradition and Future - Rodríguez-Martínez, Jorge Mario (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This essay argues that contemporary Latin American universities need to assume the task of helping to reconstruct the ethical and political background of societies whose viability is in question due to the corruption, violence, and exclusion that have affected them throughout history. Part of this mission consists in reflecting upon their societies’ socio-cultural backgrounds, in order not only to recognize their positive aspects, but also to question those political philosophical models that, responding to other contexts, have been mechanically imposed in the region. This task is illustrated with a reflection upon the political philosophy developed by Guatemalan ex-president Juan José Arévalo, an educator and philosopher who governed Guatemala from 1945 to 1950.